2018
DOI: 10.3389/fpsyg.2018.02162
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Mindfulness: Relation and Enhancement in the Classroom With Adolescents

Abstract: Emotional intelligence (EI) and mindfulness are two constructs that have been separately studied, and the relation between them still remains unclear. Research in this area has not attempted to go further into how enhancing EI and mindfulness together can achieve better improvements in this ability to attend mindfully. To bridge this knowledge gap, our research goal was to study the relationship between EI and the mindfulness competence in our study sample and to assess the impact of implementing EI and a mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…From our point of view, it is likely that the direct relationship between the practice of mindfulness and some of the dimensions of emotional intelligence, such as clarity and emotional repair, may have some influence (De la Fuente et al, 2010), as well as emotional regulation (Huang et al, 2019). On the other hand, some authors (Rodríguez-Ledo et al, 2018) have found positive relationships between the capacities of mindfulness and emotional intelligence. Rodríguez-Ledo et al (2018) point out that individuals who practice mindfulness present higher scores in intrapersonal competences (e.g., emotional self-perception or emotional self-regulation) and interpersonal competences (e.g., empathy, emotional regulation of others or coping with life’s adverse situations) that compound the emotional intelligence construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our point of view, it is likely that the direct relationship between the practice of mindfulness and some of the dimensions of emotional intelligence, such as clarity and emotional repair, may have some influence (De la Fuente et al, 2010), as well as emotional regulation (Huang et al, 2019). On the other hand, some authors (Rodríguez-Ledo et al, 2018) have found positive relationships between the capacities of mindfulness and emotional intelligence. Rodríguez-Ledo et al (2018) point out that individuals who practice mindfulness present higher scores in intrapersonal competences (e.g., emotional self-perception or emotional self-regulation) and interpersonal competences (e.g., empathy, emotional regulation of others or coping with life’s adverse situations) that compound the emotional intelligence construct.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors (Rodríguez-Ledo et al, 2018) have found positive relationships between the capacities of mindfulness and emotional intelligence. Rodríguez-Ledo et al (2018) point out that individuals who practice mindfulness present higher scores in intrapersonal competences (e.g., emotional self-perception or emotional self-regulation) and interpersonal competences (e.g., empathy, emotional regulation of others or coping with life’s adverse situations) that compound the emotional intelligence construct. In our opinion, an interesting aspect of the results obtained is the appearance of an improvement in the TEI in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, implementation of programs that target emotional intelligence, and especially the adaptability and interpersonal factors of it, should become a priority in schools to improve not only the learning processes of their students, but also their present and future well-being. Many studies have shown the effectiveness of EI school interventions in improving a student's EI, either when learning a second language [72] or in the regular school setting [73]. These interventions boost more positive classroom emotions and alleviate negative ones, facilitating the learning process of the students.…”
Section: Discussionmentioning
confidence: 99%
“…There has been emerging interest in EI among adolescents over recent years due to evidence from several studies regarding its importance in early ages for variables such as academic performance, social interaction, self-concept and social adaptation [35]; [36]; [37]. Keywords containing 'adolescent' were repeated 145 times.…”
Section: H Topics Of Interestmentioning
confidence: 99%